(untitled) (Editora Impacto Científico, 2025)
Technological evolution has driven significant changes in business operations, promoting greater efficiency, cost reduction and improved decision-making. In the wholesale segment, where competitiveness depends on the accuracy of processes and their information, automation and data analysis have become essential tools. In this context, integrated business management systems ERP Enterprise Resource Planning play a fundamental role, allowing the centralization and optimization of operational information. Among the various software available on the market, ERP TOTVS stands out as a solution widely adopted in Brazil and in several Latin American countries, offering customized parameterizations for different segments. With the increasing incorporation of emerging technologies, Artificial Intelligence AI has been a strategic differentiator, providing process automation, predictive analysis and greater reliability in information. In addition, TOTVS has easy integration with several platforms, including Mercafacil, a promotional management software, based on behavioral data for physical and online stores with Artificial Intelligence AI, which allows the customization of offers, predictions of purchasing behavior and optimization of commercial strategies. Complementing these solutions is HelpVino Inovações, a digital sommelier specializing in the wine market, which uses AI Artificial Intelligence algorithms to recommend labels, analyze consumer preferences and intelligent inventory management, contributing to an improved shopping experience and more assertive strategic decisions according to customer preferences and tastes. Given this scenario, this article aims to analyze the implementation of TOTVS ERP with integrated AI resources at Atento Bebidas, a wholesale company that predominantly sells national and imported beverages. In this way, this article contributes to the understanding of the role of ERP Enterprise Resource Planning and AI Artificial Intelligence in business management, highlighting how its application can transform wholesaler operations and generate strategic advantages, boosting competitiveness. DOI: https://doi.org/10.56238/edimpacto2025.090-015